Covalent immobilization of tyrosinase onto multi-walled carbon nanotube and its potential use in phenol biosensing - Shahir, Shafinaz (Ibnu Sina Institute, 2011)
The possibility of modifying the surface properties of multi-walled carbon nanotubes (MWCNTs) has stimulated increasing interest in their application as components in biosensors. In this sense, it is possible to employ surface modified MWCNTs as support to immobilize biomaterials such as enzymes. In this study the enzyme tyrosinase was immobilized onto functionalized MWCNTs (fMWCNTs) via covalent bonding and activity of immobilized tyrosinase was measured via electrochemical detection of phenol. MWCNTs were first treated with sulphuric acid and nitric acid with ratio 1 : 3 at 70ºC to introduce carboxylated groups (-COOH). The carboxyl moieties were then activated by treatment with a cross-linker, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) to enable tyrosinase immobilization via amide bonding. FTIR spectra of tyrosinase immobilized fMWCNTs showed the presence of peaks attributing to aliphatic C-N (1382 cm-1) and amide carbonyl (1639 cm-1) vibrations which confirmed successful covalent immobilization of tyrosinase onto fMWCNTs. Electrochemical measurements using tyrosinase-fMWCNTS-CPE revealed increasing limiting current values of reduction peak with increasing phenol concentrations at -200mV. The appearance of the reduction current indicates that the immobilization process retained the biological activity of the covalently bonded tyrosinase on fMWCNTs surface. This study has demonstrated the potential of using MWCNTs as support for enzyme immobilization and their application in biosensor technology.